Surfactant proteins and the inflammatory and immune response in the lung (Hematology Meeting Reports, 2009)
Surfactant proteins are important for regulating surfactant activity and innate host defence; in particular, polymorphisms in intron 4 of the SP-B gene and dominant mutations of SP-C have been associated with bronchopulmonary dysplasia. The innate immune system is older and consists of soluble proteins, which bind microbial products and phagocytic leukocytes resembling primitive amebae, which float through the bloodstream and migrate into tissues at sites of inflammation, or reside in tissue waiting for foreign material. The innate immune system is always active and is immediately responsive, ready to recognize and inactivate microbial products entering lungs and other tissues. Pro-inflammatory cytokines (interleukins IL-1β, IL-6 and soluble ICAM-1) are present in lung lavage fluid from day 1 in premature infants with respiratory distress and reach a peak in the second week. IL-1β induces the release of inflammatory mediators, activating inflammatory cells and up-regulating adhesion molecules on endothelial cells. ICAM-1 is a glycoprotein, promoting cell-to-cell contact. Direct contact between activated cells leads to further production of proinflammatory cytokines and other mediators. α-chemokine IL-8 is released, including neutrophil chemotaxis; the activated neutrophils mediate endothelial cytotoxicity, inhibit surfactant synthesis and release elastase.